Digital Public Service Innovation at the Ministry of Religious Affairs of Gorontalo City - Zulfa Nisa’un Nafisah; Juriko Abdussamad; Fenti Prihatini Tui (Universitas Negeri Gorontalo, 2026)
This study aims to analyze digital information technology-based public service innovation through the Tolopani All-in-One application at the Ministry of Religious Affairs Office of Gorontalo City. The focus of this research is the innovation attributes according to Rogers, which are examined through several aspects, namely relative advantage, compatibility, complexity, trialability, and observability. This study employed a qualitative approach with a descriptive research design. Data were collected through in-depth interviews with the head of the office, application administrators or managers, Tolopani coordinators, service officers, and community members as service users, supported by observation and documentation. The results indicate that the Tolopani All-in-One application has contributed to the digitalization of public services at the Ministry of Religious Affairs Office of Gorontalo City. The application offers relative advantages in terms of easy access to information, faster service delivery, and the integration of multiple services into a single system. In terms of compatibility, the application aligns with organizational needs and the demands of digital transformation, although its utilization still requires adjustments to the public's service habits. However, several challenges remain, including user adaptation, technical limitations, network and server disruptions, and difficulties in accessing the mobile application through the Play Store. The application can also be gradually adopted through socialization programs, user guidelines, and tutorial videos, while its outcomes can be observed through the transition from manual to digital service delivery. The study concludes that the Tolopani All-in-One application fulfills the characteristics of public service innovation as proposed by Rogers. Nevertheless, its implementation has not yet been fully optimized due to factors such as human resource readiness, technical conditions of the application, public preferences, and the need to align with centralized systems.